Research progress of immune checkpoint inhibitors in neoadjuvant immunotherapy for dMMR/MSI-H locally advanced colorectal cancer - Zhu Xi; Li Yang; Jiang Jun; Li Guoli; Kao Xiaoming (结直肠肛门外科)
In recent years, immune checkpoint inhibitors (ICIs) have made great progress in the treatment of colorectal cancer, particularly in the post-line and first-line treatment of dMMR/MSH-H metastatic colorectal cancer patients, demonstrating good clinical outcomes. Currently, the relevant research and exploration on the use of ICIs in neoadjuvant immunotherapy are still ongoing. This article mainly introduces the research progress of ICIs in neoadjuvant immunotherapy for dMMR/MSI-H locally advanced colorectal cancer, aiming to provide new method references for neoadjuvant immunotherapy of locally advanced colorectal cancer.